Evolução da indústria maranhense nos anos 2000 - Pereira, Maria Rosivalda da Silva (2014)
The Brazilian process of deindustrialization has been the subject of several debates over the last decade due to the behavior of the Brazilian economy in this period. However, such national debates are not a phenomenon if compared with other economies as it occurs at federal units. Thus, if was set an objective in this work. To analyze the evolution of Maranhão industry since 2000, based on the coefficients of trade openness of the state and its foreign trade flows in this period, identifying the main products exported and imported by the state as well as the origins and destinations of these products. As a result, we found that the exterior trade flows in Maranhão are medium and low technological intensity and non-industrial products. As importation it prevails products with low and medium intensity. Trade relations showed a not very diversified market with few destinations and origins of products. The export coefficients, although low, have a tendency of growth, though they are overcame by the import coefficients which have much higher rates in both industry and sector.